Challenges with Luteinizing Hormone-Releasing Hormone Agonists: Flare and Surge - Brawer, Michael K (MedReviews, LLC, 2004)
Although the mechanism behind the role of circulating androgens in the development and progression of prostatic carcinoma is not totally clear, androgen deprivation therapy remains a mainstay of treatment for this cancer. As surgical orchiectomy has fallen out of favor and the use of estrogens has been associated with cardiac toxicity, pharmacologic approaches have become even more common, namely, the use of luteinizing hormone-releasing hormone (LHRH) agonists. These agents, however, are not without side effects; the primary ones are the “flare” phenomenon, which stems from an initial surge in testosterone level and can include increased pain at metastatic sites, spinal cord compression, and even sudden death. Some studies have reported increased morbidity with the use of LHRH agonists, and while the significance of flare is not entirely known at this point, data seem to indicate that, at least in men with advanced disease, avoiding flare may be prudent.